1990
DOI: 10.1111/j.1151-2916.1990.tb07603.x
|View full text |Cite
|
Sign up to set email alerts
|

Faceting Behavior of Alumina in the Presence of a Glass

Abstract: The faceting of alumina interfaces in the presence of a glass affects both grain growth and grain-boundary mobility during liquid-phase sintering. The geometry and movement of facets that form during this sintering process are expected to play an essential role in the development of the final microstructure, in particular, by their influence on the topology of the grain boundaries which ultimately control the properties of Alz03 compacts. A new method for studying the interaction between A1203 and a glass has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…Transport of SiO 2 through the vapor phase in this manner has previously been demonstrated by Simpson and Carter. 29 It has also been discussed by Bae and Baik,8 who have demonstrated contamination of ultrapure alumina during sintering, resulting in abnormal growth. In this case, the contamination was believed to be SiO 2 from the 99.8% pure alumina crucibles.…”
Section: (1) Sources Of Silicamentioning
confidence: 93%
See 1 more Smart Citation
“…Transport of SiO 2 through the vapor phase in this manner has previously been demonstrated by Simpson and Carter. 29 It has also been discussed by Bae and Baik,8 who have demonstrated contamination of ultrapure alumina during sintering, resulting in abnormal growth. In this case, the contamination was believed to be SiO 2 from the 99.8% pure alumina crucibles.…”
Section: (1) Sources Of Silicamentioning
confidence: 93%
“…26 Sometimes, AGG results in platelike grain morphologies with the large faces usually parallel to the (0001) plane. [27][28][29] In some cases, a glassy film has been observed on these large facets, 5,7,30 which may be related to Ca segregation, 31 but other studies have found no evidence for such a film. 2,32 In contrast, further doping of CaO/SiO 2 -doped alumina with MgO hinders faceting and also inhibits AGG.…”
mentioning
confidence: 99%
“…45,46 Along this line, Opila 29 pointed out that in wet oxidation experiments (P H 2 O = 10 KPa, 1200-1400 • C) some 100 ppm sodium and aluminum impurities from Al 2 O 3 rods and hangers employed were sufficient to effect scale formation and oxidation rates of SiC. Nevertheless, the difficulties to separate water vapor effects from impurity effects prevailed 29 and also need to be addressed in the mullite system.…”
Section: Discussionmentioning
confidence: 93%
“…All these planes show high packing densities [22], the aluminium density being the highest for the (0112) plane. [25]. It is worthnoting that in the two cases the particular behavior of the (0001) plane could result from an epitaxial growth of a Si02 containing compound; as a matter of fact, it has been suggested from diffraction experiments that the thin intergranular layer may possess some short-range order governed by the structure of the grains [26,27].…”
Section: Materials 2013mentioning
confidence: 99%